The Effect of Capital Structure and Firm Growth on Profitability and Firm Value in Manufacturing Companies Listed on Indonesia Stock Exchange - Niar, Hikma (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study aims to analyze the influence of capital structure and company growth on profitability and company value in manufacturing companies on the Indonesia Stock Exchange. Design/methodology/approach – The The data analysis uses structural model testing, namely The Structure Equation Modelling (SEM), with descriptive and explanatory approaches. Finding/Results – the research results, capital structure and company growth have a positive effect on profitability, while on company value, capital structure has a positive but not significant effect, company growth has a positive and significant effect, and profitability has a positive and significant effect.The theoretical implications of this research reinforce the theory that firm value is determined not only by growth but also by the company's ability to generate profits. Originality/Value – Practical implications emphasize the importance of maintaining equity composition, as equity and profitability can be used as key indicators in assessing investment viability because they reflect a company's ability to create value. The implication of this research is that companies need to manage their capital structure optimally and ensure that the growth achieved can increase profitability, which ultimately maximizes the company's value.